Park zakonu oo. Kamilianów w Tarnowskich Górach jako przykład zagospodarowania obiektu po historycznym górnictwie galeno-galmanowym = Park at the Camilian Monastery in Tarnowskie Góry facility as an example of the historical post-calamine mining sites management - Pietrzykowski, Marcin; Śliwińska, Martyna; Krzaklewski, Wojciech; Woś, Bartłomiej (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
There are a lot of areas after historic calamine mining in the Upper Silesia region. A good way to manage such facilities, particularly in the cities, is the establishment of green area and parks. The paper presents analysis of the tree species composition and the sanitary condition of stands in park at the area of Camilian Monastery in Tarnowskie Góry.
Keywords: wyrobiska galeno-galmanowe; założenia parkowe; zieleń wysoka; post-calamine mining sites; inventorization; park